High peak power continuum generation by high-order solitons at the mid-infrared wavelength in a photonic crystal fiber. (10th March 2015) - Yuan, Jinhui; Zhou, Guiyao; Liu, Hongzhan; Xia, Changming; Sang, Xinzhu; Yu, Chongxiu; Wang, Kuiru; Yan, Binbin; Han, Ying; Hou, Lantian
Abstract: A photonic crystal fiber (PCF) is fabricated from silica material purified by the complexing method of rectification and adsorption in our laboratory. The parameters of pump pulses and fiber length are optimized in the experiment, and the nonlinear optical process of the high-order soliton generation is studied. The high peak power continuums at the mid-infrared wavelength are generated by the overlap among the high-order soliton peaks. Specifically, when a PCF with a length of 60 cm is used, the conversion efficiency η and bandwidth B of the continuum generated can be up to 65% and 358 nm, and the corresponding peak power P peak-o and pulse width W p are 144 kW and 30 fs. It is believed that the high peak power and broadband mid-infrared continuum can be used as short pulse sources, which will find important applications in biophotonics and ultrafast science and technology.